1970
DOI: 10.1029/rg008i003p00473
|View full text |Cite
|
Sign up to set email alerts
|

Seismic radiation from explosions in prestressed media and the measurement of tectonic stress in the Earth

Abstract: The radiation field from explosions in a prestressed medium can be theoretically predicted on the basis of a dynamical theory of stress relaxation in the vicinity of the shock-induced fracture zone created by an explosion. The field consists of the normal compressional wave field resulting from the conversion of the shock wave to an elastic wave plus an anomalous part due to the release of strain energy. In this study we consider the nature of the radiation field to be expected from such a source in an inhomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…This problem has been considered before by Archambeau [1972] and by Burridge and Alterman [1972] and was originally introduced as a model to explain the SH waves which are observed to be generated by nuclear explosions [ToksiOz et al, 1965;Press and Archambeau, 1962;Archambeau and Sammis, 1970]. (More recently, Aki and Tsai [ 1972] have shown that induced tectonic stress release is a more likely mechanism.)…”
mentioning
confidence: 99%
“…This problem has been considered before by Archambeau [1972] and by Burridge and Alterman [1972] and was originally introduced as a model to explain the SH waves which are observed to be generated by nuclear explosions [ToksiOz et al, 1965;Press and Archambeau, 1962;Archambeau and Sammis, 1970]. (More recently, Aki and Tsai [ 1972] have shown that induced tectonic stress release is a more likely mechanism.)…”
mentioning
confidence: 99%
“…In this article we also investigate the complexity of seismic radiation patterns and the generation of transversely polarized (SH) waves by an explosion in an azimuthally anisotropic medium. The causes of the azimuthal dependence of radiation patterns of P-, SV-, and Rayleigh waves and the generation of SH-and Love waves by underground nuclear explosions have been studied extensively (Kisslinger, Mateker & McEvilly 1961;Archambeau & Sammis 1970;Toksoz & Kehrer 1972;Mass6 1981;Wallace, Helmberger & Engen 1983;Gupta & Blandford 1983;Lynnes & Lay 1988;Johnson 1988). Various mechanisms, including tectonic strain energy release by relaxation or triggering of an earthquake, dislocation across cracks, spallation and 'slapdown', and scattering from heterogeneities, have been proposed and found to explain some of the data.…”
Section: Introductionmentioning
confidence: 99%
“…Such a representation is very general, and can be obtained for a variety of source models, including relaxation sources (e.g. Archambeau 1964Archambeau , 1968Minster 1973;Burridge 1975), dislocation sources (Burridge 1969;Brune 1970;Savage 1966), as well as for underground nuclear explosions (Archambeau 1964;Archambeau & Sammis 1970;Haskell 1967). However, in most cases a multipolar representation is easily reached only in a particular coordinate system satisfying the conditions of symmetry of the source.…”
Section: Introductionmentioning
confidence: 99%